Implikasi Pendidikan Karakter Bagi Anak Perspektif Q.S. Al-Baqarah ayat 83 - Fauzan, Farhan Ahmad (Atthulab: Islamic Religion Teaching and Learning Journal, 2021)
Abstract: Al-Quran is the kalamullah that was sent down through the Prophet Muhammad as a source of Islamic teachings which contains various kinds of rules as well as instructions in living the life of a Muslim. Q.S Al-Baqarah verse 83 is one of the verses that discusses the agreement between the Children of Israel and Allah SWT. In this verse, there are several points of agreement that the Children of Israel must always do, but in the end they deny and are among those who do wrong. Parents as someone who is gifted by Allah SWT should educate their children as best they can. Because children’s education is not the only responsibility of educational institutions. In this verse, there are several points that can be used as a basis for educating children. The purpose of this study was (1) Knowing the interpretation of the muffasir QS al-Baqarah verse 83 (2) Knowing character education for children according to QS al-Baqarah verse 83 (3) Knowing the implementation of children’s education contained in the Al-Qur’an Surat al-Baqarah verse 83 the implication in character education Â Abstrak: Al-Quran adalah kalamullah yang diturunkan melalui Nabi Muhammad sebagai sumber ajaran Islam yang berisikan berbagai macam aturan juga petunjuk dalam menjalani kehidupan seorang muslim. Q.S Al-Baqarah ayat 83 merupakan salah satu ayat yang membahas perjanjian Bani Israil dengan Allah SWT. Pada ayat tersebut terdapat beberapa poin perjanjian yang harus senantiasa Bani Israil lakukan, namun pada akhirnya mereka mengingkari dan termasuk orang-orang yang dzalim. Orang tua sebagai seseorang yang dikaruniakan anak oleh Allah SWT sudah selayaknya mendidik anak-anak mereka sebaik mungkin. Karena pendidikan anak bukan hanya tanggung jawab lembaga pendidikan. Pada ayat ini terdapat beberapa poin yang dapat dijadikan landasan untuk mendidik anak. Tujuan penelitian ini adalah untuk (1) Mengetahui penafsiran para muffasir Q.S al-Baqarah ayat 83 (2) Mengetahui pendidikan karakter bagi anak menurut Q.S al-Baqarah ayat 83 (3) Mengetahui implementasi pendidikan anak yang terkandung pada AlQurâ€™an Surat al-Baqarah ayat 83 implikasinya dalam pendidikan karakter.